Solvent‐Free Ball‐Milling Biginelli Reaction by Subcomponent Synthesis. Issue 32 (8th October 2015) - Sahoo, Prasit Kumar; Bose, Anima; Mal, Prasenjit
Abstract: We report here an understanding of systems chemistry on small molecules through covalent mechanochemistry. As a proof‐of‐concept, the multicomponent Biginelli reaction by subcomponent synthesis was considered as a model system. Reactions were performed under solvent‐free, metal‐free, mechanochemical (ball milling) and ambient laboratory conditions. Br + ‐catalyzed oxidation of benzyl alcohols led to the product benzaldehydes and byproduct H + which were further promoted as component and catalyst, respectively, for a cascade transformation to dihydropyrimidones within the same reaction pot. Remarkably, in solution, the reaction system could not be reproduced at room temperature even after 24 h. Abstract : Under solvent‐free ball‐milling conditions, multicomponent Biginelli reactions for the synthesis of dihydropyrimidones were performed by subcomponent synthesis of reagents (aldehydes) and catalyst (H + ) from Br + oxidation of benzyl alcohols.